Persuasive discourse through lexical choices used by experts in The Social Dilemma (2020) - Risma Fadilla; Cipto Wardoyo; Dian Nurrachman (EduLite: Journal of English Education, Literature and Culture, 2026)
This study investigated how expert speakers in The Social Dilemma (2020) constructed persuasive discourse through lexical choices. It aimed to identify the lexical strategies that realized Aristotle’s rhetorical appeals (ethos, pathos, and logos) and to classify them using Kuna (2018) seven persuasive categories. A convergent mixed-methods design integrated corpus-assisted discourse analysis with qualitative rhetorical interpretation. Expert utterances were extracted from the documentary transcripts and processed with Sketch Engine to identify and quantify recurring lexical items. The findings showed that Certainty and Emotional Involvement were the most prominent categories. Lexical items such as know, predict, you, we, manipulate, control, and existential combined epistemic authority, personal address, and threat framing to convert abstract technological processes into immediate social risks. General Positive Value terms were frequently recontextualized ironically, whereas Testedness and Authenticity/Credibility strengthened evidence-based and insider claims. These patterns demonstrate that persuasion in the documentary emerged from the interaction of lexical frequency, discourse context, and rhetorical function rather than from isolated words. Future researchers should compare several technology documentaries and integrate verbal, visual, and auditory modes to test the transferability of these lexical patterns.